Zero‐Bias Power‐Detector Circuits based on MoS2 Field‐Effect Transistors on Wafer‐Scale Flexible Substrates. Issue 48 (17th February 2022) - Reato, Eros; Palacios, Paula; Uzlu, Burkay; Saeed, Mohamed; Grundmann, Annika; Wang, Zhenyu; Schneider, Daniel S.; Wang, Zhenxing; Heuken, Michael; Kalisch, Holger; Vescan, Andrei; Radenovic, Alexandra; et al.
Abstract: The design, fabrication, and characterization of wafer‐scale, zero‐bias power detectors based on 2D MoS2 field‐effect transistors (FETs) are demonstrated. The MoS2 FETs are fabricated using a wafer‐scale process on 8 μm‐thick polyimide film, which, in principle, serves as a flexible substrate. The performances of two chemical vapor deposition MoS2 sheets, grown with different processes and showing different thicknesses, are analyzed and compared from the single device fabrication and characterization steps to the circuit level. The power‐detector prototypes exploit the nonlinearity of the transistors above the cut‐off frequency of the devices. The proposed detectors are designed employing a transistor model based on measurement results. The fabricated circuits operate in the Ku‐band between 12 and 18 GHz, with a demonstrated voltage responsivity of 45 V W −1 at 18 GHz in the case of monolayer MoS2 and 104 V W −1 at 16 GHz in the case of multilayer MoS2, both achieved without applied DC bias. They are the best‐performing power detectors fabricated on flexible substrate reported to date. The measured dynamic range exceeds 30 dB, outperforming other semiconductor technologies like silicon complementary metal–oxide–semiconductor circuits and GaAs Schottky diodes. Abstract : Power‐detector circuits are realized based on MoS2 channel transistors fabricated on flexible polyimide substrates. The work compares the DC and radio‐frequency performance of multilayer and monolayer wafer‐scale grown MoS2 for power detection and shows that both materials allow the fabrication of circuits that work at GHz frequencies with excellent dynamic range and responsivity.